Rolnictwo w myśli politycznej Stronnictwa Chłopskiego (1926–1931) - Podgajna, Ewelina (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
The Peasant Party was established in January 1926 as a result of a secession by the Polish Peasant Parties Association “Liberation” and “People’s Unity”. It quickly gained huge support in society and became the third power in the Peasant movement. The farm was to become the core of the most important branch of the national economy – agriculture. The Peasant Party’s leadership believed that the way to power in the country was through the reforms for peasants which were promised to them after regaining independence. The Party and its Parliamentary Club suggested the regeneration of the social and economic system. The basis for this regeneration was intended to be, firstly, making small farms the basis of the national economy; secondly, carrying out agricultural reform; thirdly, socialising the basic branches of industry and mining; fourthly, popularising the agricultural and commercial cooperative movements; and fifthly, developing and disseminating all educational reforms, particularly those concerning vocational and agricultural education.